Analisis Penerimaan Teknologi Pembelajaran Dalam Jaringan Menggunakan Unified Theory of Acceptance And Use of Technology 2 - Rulandi, Thomas; Tambotoh, Johan J.C. (J-SAKTI (Jurnal Sains Komputer dan Informatika), 2023)
Online learning is an option during the Covid-19 pandemic by utilizing the Google Meet application as a liaison for online learning. Therefore, this study measures the acceptance of learning technology in the network, especially using the Google Meet application using the UTAUT 2 model. This study aims to see what things affect the acceptance of online learning. This model uses several variables, namely Performance Expectancy, Effort Expectancy, Social Influence, Facilitating Conditions, Hedonic Motivation, Price Value, and Habit. This study uses a survey quantitative approach to collect data and analyze data using Structural Equation Modeling. In this study, three accepted hypotheses were obtained, namely H4, H7 and H8 and four were not accepted, namely H1, H2, H3 and H6.